KAEDAH MELUKIS GAMBARAJAH: SATU PENDEKATAN DALAM PROSES PENYELESAIAN MASALAH MATEMATIK - Ariffin, Arihasnida; Baisar, Zainora; Hamzah, Norhasyimah; Rubani, Siti Nur Kamariah; Subramaniam, Tamil Selvan (Online Journal for TVET Practitioners, 2018)
The purpose of this study was to investigate the effect of the drawing method on the problem solving of primary school mathematics. The objective of this study is to identify the achievement of students before and after using the drawing diagram as a method. The design of this study is a quasi-experimental using pre-test and post-test. The sample of this study consists of 39 students in Kluang Religious Primary School, Johor. The instrument used is a set of mathematical tests. The data were analyzed using the Microsoft Excel 2010 software to obtain the percentage of the test. The analysis showed that the percentage of students’ achievement was higherin post-test, after using the drawing diagram method in mathematical problem solving. The findings of this study show that the method of drawing a diagram in mathematical problem solving is more effective and can improve students' achievement in mathematics subject.